Bioprospecting of extremophilic perchlorate‑reducing bacteria: report of promising Bacillus spp. isolated from sediments of the bay of Cartagena, Colombia (2023)
Three extremophile bacterial strains (BBCOL-009, BBCOL-014 and BBCOL-015), capable of degrading high concentrations of perchlorate at a range of pH (6.5 to 10.0), were isolated from Colombian Caribbean Coast sediments. Morphological features included Gram negative strain bacilli with sizes averaged of 1.75 × 0.95, 2.32 × 0.65 and3.08 × 0.70 μm, respectively. The reported strains tolerate a wide range of pH (6.5 to 10.0); concentrations of NaCl (3.5 to 7.5% w/v) and KClO4− (250 to 10000 mg/L), reduction of KClO4 − from 10 to 25%. LB broth with NaCl (3.5–30% w/v) and KClO4ˉ(250-10000 mg/L) were used in independent trialsto evaluate susceptibility to salinity and perchlorate,respectively. Isolates increased their biomass at 7.5 % (w/v) NaCl with optimal development at 3.5 % NaCl. Subsequently, ClO reduction was assessed using LB medium with 3.5% NaCl and 10000 mg/L ClO4 BBCOL-009, BBCOL-014 and BBCOL-015 achieved 10%, 17%, and 25% reduction of ClO4 respectively. The 16 S rRNA gene sequence grouped them as Bacillus flexus T6186-2, Bacillus marisflavi TF-11 (T), and Bacillus vietnamensis 15 − 1 (T) respectively, with < 97.5% homology. In addition, antimicrobial resistance to ertapenem, vancomycine, amoxicillin clavulanate, penicillin, and erythromycin was present in all the isolates, indicating their high adaptability to stressful environments. The isolated strains from marine sediments in Cartagena Bay, Colombia are suitable candidates to reduce perchlorate contamination in different environments. Although the primary focus of the study of perchlorate-reducing and resistant bacteria is in the ecological and agricultural realms, from an astrobiological perspective, perchlorate-resistant bacteria serve as models for astrobiological investigations.